Partie orientale du Canada - Le Rouge, Georges-Louis (A Paris, Rue des Grands Augustins, 1756)
Hand coloured. Prime meridian Ferro. Compass rose. Relief shown pictorially. Bar scale in marine leagues and English miles. Includes legend on top edge. Explanation of boundaries in French and German. Includes table of comparative latitudes and longitudes. "Traduitte de l'Angloise de la carte de Jefferys publiée a Londres en May 1755" (title). CNS map no. 128.